Case Report: Prophylactic Plate Fixation for Incomplete Atypical Ulnar Fractures Resulting From the Use of Denosumab for Bone Metastases - Murai, Atsuro; Tada, Kaoru; Nakajima, Tadahiro; Akahane, Mika; Matsuta, Masashi; Nakamura, Yuta; Tsuchiya, Hiroyuki (Frontiers in Endocrinology, 2022)
Patients with bone metastases are treated with long-term administration of bone resorption inhibitors such as bisphosphonates, zoledronic acid, and denosumab. However, it has been reported that resorption inhibitors sometimes cause fractures, such as atypical femoral fractures (AFF). In recent years, there have also been increasing reports of atypical ulnar fractures (AUF) caused by bone resorption inhibitor usage. Treatment of AUFs is complicated, especially when they occur in patients with bone metastases, because it is difficult to discontinue bone resorption inhibitor treatment without the risk of aggravating metastatic lesions. Prophylactic surgery is recommended in AFF when fractures are predicted, but there are few reports of prophylactic surgery for AUF. In this report, we perform prophylactic plate fixation of an incomplete AUF in a 74-year-old woman who had undergone 6 years of denosumab treatment for bone metastasis of thyroid cancer. She was free of fractures for 2 years after the surgery without discontinuing the use of denosumab, and her forearm function was adequate. AUFs are rare, but once they occur are difficult to treat, so oncologists who treat bone metastases need to pay attention to find this incomplete atypical ulnar fractures before the fracture occurs. We believe that detecting the possibility of a fracture before it occurs and performing prophylactic surgery can help extend the patient's healthy lifespan.